Treatment of Chronic Posttraumatic Leg Injury Using Autologous Fat Graft - Fabio Caviggioli; Francesco Maria Klinger; Valeriano Vinci; Guido Cornegliani; Marco Klinger (Case Reports in Medicine)
We present the results obtained in a case of a 20-year-old Caucasian woman with a posttraumatic injury “hard-to-heal” of the left leg treated using autologous fat graft. Considering our experience in treatment of chronic posttraumatic ulcers by autologous fat graft, we decided to use this surgical technique to induce a regenerative effect in this young patient. We have had complete wound closure with only a single surgical procedure after 1 month; after the second intervention of autologous fat graft we observed an improvement in the quality of the scar tissue. The patient satisfaction was excellent. The results were long lasting and remained virtually unchanged after 1 year.